2010
DOI: 10.1128/iai.00138-10
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate Binding of Immune Regulator Factor H Is Associated with Sensitivity ofBorrelia lusitaniaeto Human Complement

Abstract: Spirochetes belonging to the Borrelia burgdorferi sensu lato complex differ in resistance to complementmediated killing by human serum. Here, we characterize complement sensitivity of a panel of B. lusitaniae isolates derived from ticks collected in Germany and Portugal as well as one patient-derived isolate, PoHL. All isolates are highly susceptible to complement-mediated lysis in human serum and activate complement predominantly by the alternative pathway, leading to an increased deposition of complement com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 65 publications
(109 reference statements)
3
17
0
Order By: Relevance
“…Most of the complement-positive spirochetes showed extensive bleb formation when exposed to human serum, while a few cells stained negative for complement but were positive in the DAPI stain. Those spirochetes most likely represent “cell ghost” as previously described for serum susceptible B. garinii and B. lusitaniae strains [43], [49]. When spirochetes were incubated with heat-inactivated NHS, the cell morphology remained completely intact and deposition of complement was not detectable by immunofluorescence microscopy (data not shown).…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…Most of the complement-positive spirochetes showed extensive bleb formation when exposed to human serum, while a few cells stained negative for complement but were positive in the DAPI stain. Those spirochetes most likely represent “cell ghost” as previously described for serum susceptible B. garinii and B. lusitaniae strains [43], [49]. When spirochetes were incubated with heat-inactivated NHS, the cell morphology remained completely intact and deposition of complement was not detectable by immunofluorescence microscopy (data not shown).…”
Section: Resultssupporting
confidence: 57%
“…Irrespective of whether they displayed a serum-sensitive or resistant phenotype, all three B. valaisiana isolates acquired CFHR-1 and strain Bv9, in addition, also bound CFHR2 from human serum. Despite binding of these complement regulators, Bv9 and VS116 failed to regulate complement activation, thus permitting bacteriolysis as previously shown for B. lusitaniae [49]. More interestingly, isolate ZWU3 Ny3 bound neither complement regulators of the alternative pathway CFH and FHL1, nor of the classical and lectin pathways, C4Bp and C1-Inh, respectively.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Interaction with CFH has previously been reported for CRASP-4/ErpC and other closely related Erp proteins, for example, OspE paralogs from B. burgdorferi , B. afzelii , B. spielmanii , B. garinii , B. lusitaniae , B. turdi , B. tanukii , and B. japonica [3, 6, 11, 12, 33, 35, 37, 38, 43, 51, 5558]. Here we demonstrate that recombinant CRASP-4 bound CFH in ELISA or ligand affinity blot experiments using borrelial cell lysates (Figures 2 and 3(b)).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the complete abrogation of activation of inflammatory signaling in the absence of MyD88 implied that TLR2 did not activate a MyD88-independent pathway for signaling (19,20). However, more recently, multiple studies have shown that TLR2 is present in intracellular compartments and is involved in signaling from these compartments (3,(21)(22)(23)(24)(25)(26). Stimulation with TLR2 specific lipopeptides was shown to lead to the activation of type I interferons and proinflammatory cytokines, such as IL-6, whose activation and release was dependent on endosomal acidification (23,26).…”
mentioning
confidence: 99%